Development of A Simulation Lab Service System, Kuakarun Faculty of Nursing, Navamindradhiraj University - Onlamool, Surat; tupanich, walaya (Vajira Nursing Journal, 2024)
This study aimed to develop a simulation lab service system at Kuakarun Faculty of Nursing, Navamindradhiraj University. The research consisted of 3 phases: system analysis, system design, and system trial/quality testing. The sample group comprised 77 people, including 65 nursing students and 12 nursing instructors selected with purposive sampling. Data collection employed semi-structured interviews, a system quality assessment, and an assessment of system service use satisfaction. The research instruments were checked for content validity by 5 experts. The Index of Objective Congruence (IOC) was .67 - 1.00, and reliability was measured by Cronbach's alpha coefficient at .82 and .83, respectively. Data were analyzed using descriptive statistics, dependent t-test (p-value < .05) and content analysis. The research findings revealed the following: 1) The problems in the service system of the simulation lab included insufficient and outdated equipment compared to real hospital wards, small space unable to accommodate large groups of students, limited operating hours (8:00 AM - 4:00 PM) preventing students from coming to use the services on time after classes, and a shortage of staff. 2) The design of this simulated lab service system aimed to provide professional services, allocate adequate personnel, budget, and materials/equipment. Services were arranged before, during, and after classes, with evaluation of service quality and user satisfaction to guide improvements; 3) The developed service system was of high quality, and users expressed high to very highest satisfaction with the system. Based on the findings, service providers should use the simulation lab service system continuously and expand the use the simulation lab service system to other units to promote high-quality, convenient, and responsive services for users as needed.